Association between perinatal depression in mothers and the risk of childhood infections in offspring: a population-based cohort study - West Joe; Gibson Jack E; Ban Lu; Tata Laila J (BMC, 2010)
Abstract Background Previous studies have suggested that children of mothers who experience depression during the perinatal period may have more infections, but such studies are few in number and none have been carried out in the United Kingdom (UK) population. The aim of this study was to investigate the association between perinatal depression in mothers and the risk of childhood infections in offspring in the UK general population. Methods We used data from The Health Improvement Network (THIN), a large database of electronic primary care medical records to conduct a cohort study among all first-born singleton children born and enrolled in THIN between 1988 and 2004. We used Poisson regression to compare the incidence of gastrointestinal infections and lower respiratory tract infections reported between birth and age 4 years among children of mothers with a record of perinatal depression with those born to mothers with no such history. Results Children of mothers with perinatal depression had a 40% increased risk of gastrointestinal infections and a 27% increased risk of lower respiratory tract infections compared with children of mothers without perinatal depression (incidence rate ratios = 1.40 and 1.27; 95% confidence intervals 1.37-1.42 and 1.22-1.32, respectively). On restricting to antibiotic-treated infections there was a slight increase in the magnitude of association with gastrointestinal infections but a decrease in that with lower respiratory tract infections (incidence rate ratios = 1.47 and 1.19; 95% confidence intervals 1.34-1.61 and 1.11-1.27, respectively). Conclusions Maternal perinatal depression is associated with increased rates of childhood gastrointestinal infections, particularly more severe infections, and lower respiratory tract infections in the UK. Preventing maternal perinatal depression may avoid substantial morbidity among offspring, although further work is also needed to investigate the detailed reasons for these findings.